"Primeiro damismo" no Brasil: uma história das mulheres na cultura política nacional (1889-2010) - Rodrigues, Dayanny Deyse Leite (2021)
This doctoral thesis aims to stimulate new reflections about the subjects that compose the political field, like the first ladies, and to emphasize the importance of the power relations that surround this field. Thus, when telling a story of women in correlation with the "primeiro-damismo” in Brazil, the objective was to understand the institutionalization of this phenomenon in Brazilian territory, as well as its perpetuation and reinvention during the republican period. Initially, it is important to point out the conceptual inexistence of the term “primeiro-damismo” in historiographical production, despite the inattentive and inappropriate use of this expression. Thus, the problems that guided this research were: how to define "primeiro-damismo" and how this phenomenon was inserted in the Brazilian political culture. To this end, an analysis of the performance of the Brazilian first ladies was carried out in a section that extends from 1989, the year that marks the beginning of the republican period, until 2010, when the first woman is elected President of the Republic, seeing them as active agents in the political field. Based on such analysis, “primeiro-damismo” was defined as a political phenomenon, characterized by a set of practices exercised by the wives of acting rulers, in the Executive Branch, which can be pointed out as a strategy, when the first ladies sought to legitimize the spouse's ideology or political project, but also as a tactic, by circumventing the rational and functional organization of governability proposed by the State. This phenomenon was constituted and perpetuated under the sign of gender hierarchies, which marked the patriarchal society, characteristic of Brazilian society. In this sense, this work dialogued with the theoretical assumptions of “Renewed Political History”, appropriating the concepts of Strategy, Tactics, Political Culture and Political Capital from the perspective of power relations, which extends beyond institutions and the State. In this perspective, the research sought to retell the history of the Brazilian Republic experienced by other subjects, or rather, by subjects made invisible by history and historiography, the first ladies, proposing reflections based on the history of Women. As sources, this work used official documents, press (newspapers and magazines), biographical and autobiographical writings. Finally, based on the results obtained, the symbolic importance of the social figure of the first ladies within the political field and the practices developed by them, which, here, were called "primeirodamismo", were pointed out. In their strategic bias, many of these actions went in line with the political ideals of the State, whose function was precisely to legitimize them. The tactics could be observed in "small" actions, from the power of influence that many first ladies had with their husbands, acting behind the scenes as a fundamental part in the political game, to the construction of their own political capital, visible in the protagonist actions developed by several of them.